Epstein–Barr Virus—Oral Bacterial Link in the Development of Oral Squamous Cell Carcinoma - Daniela Núñez-Acurio; Denisse Bravo; Francisco Aguayo (Pathogens, 2020)
Oral squamous cell carcinoma (OSCC) is the most common type of oral cancer. Its development has been associated with diverse factors such as tobacco smoking and alcohol consumption. In addition, it has been suggested that microorganisms are risk factors for oral carcinogenesis. Epstein–Barr virus (EBV), which establishes lifelong persistent infections and is intermittently shed in the saliva, has been associated with several lymphomas and carcinomas that arise in the oral cavity. In particular, it has been detected in a subset of OSCCs. Moreover, its presence in patients with periodontitis has also been described. Porphyromonas gingivalis (P. gingivalis) is an oral bacterium in the development of periodontal diseases. As a keystone pathogen of periodontitis, P. gingivalis is known not only to damage local periodontal tissues but also to evade the host immune system and eventually affect systemic health. Persistent exposure to P. gingivalis promotes tumorigenic properties of oral epithelial cells, suggesting that chronic P. gingivalis infection is a potential risk factor for OSCC. Given that the oral cavity serves as the main site where EBV and P. gingivalis are harbored, and because of their oncogenic potential, we review here the current information about the participation of these microorganisms in oral carcinogenesis, describe the mechanisms by which EBV and P. gingivalis independently or synergistically can collaborate, and propose a model of interaction between both microorganisms.